INFORMATION, AUTHORITY, AND SMOOTH COMMUNICATION IN ORGANIZATIONS - Dezsö Szalay; Inga Deimen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Two divisions of a firm, overarched by a headquarters, are engaged in a decision problem. Division one obtains information and informs division two who has the formal authority to make the decision. Headquarters guides the decision process by affecting the quality of information that division one obtains. In equilibrium, division one honestly communicates the inferences drawn from its observations, but not the underlying observations themselves and division two takes the advice at face value. The communication equilibrium involves smooth strategies and is outcome equivalent to delegation: the informed party gets its way, regardless of the allocation of formal authority.
Keywords: D82; D83; D86; 330